Komposisi muzik "Electroacoustic" Gua Kapow - Asas, ak. Ranyaw. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Sounds of nature bring inspiration to every individual who appreciates them. Besides its famous legend, Gua Kapow (Fairy Cave) is still a hidden natural treasure which is fully unexplored. Therefore, I decided to do recordings of sounds in and around the cave and use them as materials in my electroacoustic music composition, "Gua Kapow".